Determinants of Technical Efficiency of Small Scale Sunflower Oil Processing Firms in Tanzania: One Stage Stochastic Frontier Approach - Njiku, Anastasia R.; Nyamsogoro, Ganka D. (Asian Journal of Economics and Empirical Research, 2018)
Sunflower oil processing firms have recently captured the attention of many scholars due to their contributions along the value chain. Despite their contributions, 75% of them operate under capacity with steadily declining technical efficiency. This paper estimates the technical efficiency of sunflower oil processing firms in Tanzania and the factors contributing to their inefficiency. We used firm-level average production data for three years from 2013 to 2015 collected from a sample of 219 Sunflower oil processing firms. Data were analyzed using one Stage Stochastic Production Frontier with inefficiency effect model under the Maximum Likelihood Estimate (MLE) technique. We found that Capital and materials input factors of production contributed statistically significantly to the output of the firms under the study. In the same way, firm age, location, ownership type, age and education of the owner were found significant determinants of technical efficiency in sunflower oil processing firms in Tanzania. The findings in this paper imply that there is a need to adopt efficiency-enhancing measures including replacement of existing old machines since inefficiency increases with age; affordable industrial locations for easy accessibility and support services; and promotion of proper entrepreneurial education to owners.